Lung cancer: (Current state 20 years later) - Martínez, José; De Stefani, Eduardo; Piñeyro, José A.; Touya, Eduardo; Peixoto, J. J.; Musé, Ignacio Miguel (Cirugía del Uruguay, 1982)
The subject C.B.P. He was magnificently treated by Bonifacio Urioste at the XIII Uruguayan Congress of Surgery in 1962 (373). When one reads this work, one observes that there have not been great variations in the field of surgery. For 40 years there have been no technical changes that mean a greater curative efficacy of it. Perhaps you are witnessing a tactical change; limited operations are gaining ground and today occupy a priority place in the therapeutic scheme.